2005
DOI: 10.1038/modpathol.3800386
|View full text |Cite
|
Sign up to set email alerts
|

PLAG1 gene alterations in salivary gland pleomorphic adenoma and carcinoma ex-pleomorphic adenoma: a combined study using chromosome banding, in situ hybridization and immunocytochemistry

Abstract: Pleomorphic adenoma is the most common benign tumor of the salivary glands. It has marked histological diversity with epithelial, myoepithelial and mesenchymal-type cells arranged in a variety of architectural and differentiation patterns. Pleomorphic adenoma gene 1 (PLAG1), shown to be consistently rearranged in pleomorphic adenomas, is activated by chromosomal translocations involving 8q12, the chromosome region that is most frequently affected in these tumors. In this study, we evaluated PLAG1 involvement i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
132
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(141 citation statements)
references
References 21 publications
6
132
1
2
Order By: Relevance
“…22 Among these, carcinoma ex pleomorphic adenomas may still demonstrate PLAG1 alterations. 23 Finally, although an exceedingly rare phenomenon, pleomorphic adenoma can metastasize and give rise to a so-called benign metastasizing pleomorphic adenoma. 24 However, none of the reported cases has metastasized to the soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…22 Among these, carcinoma ex pleomorphic adenomas may still demonstrate PLAG1 alterations. 23 Finally, although an exceedingly rare phenomenon, pleomorphic adenoma can metastasize and give rise to a so-called benign metastasizing pleomorphic adenoma. 24 However, none of the reported cases has metastasized to the soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed tumors show PLAG1 gene rearrangement in 37-72 % of cases [15,29], suggesting a genetic relationship to their salivary gland counterparts, as up to 88 % of salivary pleomorphic adenoma [30] and up to 63-75 % of carcinoma ex pleomorphic adenoma have PLAG1 gene alterations [19,30].…”
Section: Geneticsmentioning
confidence: 99%
“…Few CA-ex-PA have been evaluated for PLAG1 status [11,12,[14][15][16]. Martins et al [15] found PLAG1 rearrangement in 3 cases and trisomy 8 without gene alteration in 1 case among 4 selected CA-ex-PA that were known to have karyotypic deviations of chromosome 8 [15].…”
Section: Introductionmentioning
confidence: 99%